2012
DOI: 10.1029/2012gl053793
|View full text |Cite
|
Sign up to set email alerts
|

Elevated pore pressure and anomalously low stress in regions of low frequency earthquakes along the Nankai Trough subduction megathrust

Abstract: Recent seismic reflection and ocean bottom seismometer (OBS) studies reveal broad regions of low seismic velocity along the Nankai subduction plate boundary megathrust offshore SW Japan. These low velocity zones (LVZ's) extend ∼55 km landward from the trench, corresponding to depths of >∼10 km below sea floor. Here, we estimate the in‐situ pore pressure and stress state within these LVZ's by combining P‐wave velocities obtained from the geophysical surveys with new well‐constrained empirical relations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
157
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(171 citation statements)
references
References 30 publications
14
157
0
Order By: Relevance
“…In addition to its intrinsic weakness due to the abundance of clay minerals, the low porosity and permeability of the claystone sample likely resulted in an increase in pore pressure during its compression, which may have further weakened this sample and promoted its slow failure (Takahashi et al 2013). It has recently been suggested that the slow slip events or very low frequency earthquakes observed within the Nankai Trough accretionary prism or along the shallow décollement (Ito and Obara 2006;Sugioka et al 2012) occur in regions of elevated pore fluid pressures (Park et al 2010;Kitajima and Saffer 2012). Because claystone is likely under a high pore water pressure during its compression, and also because it fails slowly, faulting in claystone layers is a possible source for such slow slip events or very low frequency earthquakes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its intrinsic weakness due to the abundance of clay minerals, the low porosity and permeability of the claystone sample likely resulted in an increase in pore pressure during its compression, which may have further weakened this sample and promoted its slow failure (Takahashi et al 2013). It has recently been suggested that the slow slip events or very low frequency earthquakes observed within the Nankai Trough accretionary prism or along the shallow décollement (Ito and Obara 2006;Sugioka et al 2012) occur in regions of elevated pore fluid pressures (Park et al 2010;Kitajima and Saffer 2012). Because claystone is likely under a high pore water pressure during its compression, and also because it fails slowly, faulting in claystone layers is a possible source for such slow slip events or very low frequency earthquakes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using seismic reflection, ocean bottom seismometers, and seismic tomography suggest that the source regions of low-frequency seismic events correspond to zones of elevated fluid pressure, suggesting a very low stress drop during these events (Ito and Obara 2006b;Shelly et al 2006;Matsubara et al 2009;Kitajima and Saffer 2012). Low-frequency tremors and earthquakes at depths of 30 to 45 km and temperatures of 400°C to 550°C under increased fluid pressures are generally assumed to result from dehydration of the subducting oceanic plate (Obara 2002;Shelly et al 2006;Matsubara et al 2009).…”
Section: Geological and Experimental Aspects Of Slow Earthquakesmentioning
confidence: 99%
“…Based on our observation that residual shear strength generally increases with depth, significant excess pore pressures would be required in this unit to make it weak enough to be mechanically favorable for hosting a major thrust fault [Le Pichon et al, 1993]. Recent estimates of in situ pore pressure at the base of the outer wedge determined by relationships between P wave velocity, porosity, and effective mean stress document excess pore pressures of 45-91%, or ¼ $0.7-0.95 [Kitajima and Saffer, 2012]. We employ these values of , , and in a Coulomb wedge calculation for the outer wedge area.…”
Section: Outer Wedgementioning
confidence: 99%